Angelica Sinensis promotes myotube hypertrophy through the PI3K/Akt/mTOR pathway - Yeh, Tzu-Shao (BMC Complement Altern Med, 2014)
BACKGROUND: Angelica Sinensis (AS), a folk medicine, has long been used in ergogenic aids for athletes, but there is little scientific evidence supporting its effects. We investigated whether AS induces hypertrophy in myotubes through the phosphatidylinositol 3-kinase (PI3K)/Akt (also termed PKB)/mammalian target of the rapamycin (mTOR) pathway. METHODS: An in vitro experiment investigating the induction of hypertrophy in myotubes was conducted. To investigate whether AS promoted the hypertrophy of myotubes, an established in vitro model of myotube hypertrophy with and without AS was used and examined using microscopic images. The role of the PI3K/Akt/mTOR signaling pathway in AS-induced myotube hypertrophy was evaluated. Two inhibitors, wortmannin (an inhibitor of PI3K) and rapamycin (an inhibitor of mTOR), were used. RESULT: The results revealed that the myotube diameters in the AS-treated group were significantly larger than those in the untreated control group (P < 0.05). Wortmannin and rapamycin inhibited AS-induced hypertrophy. Furthermore, AS increased Akt and mTOR phosphorylation through the PI3K pathway and induced myotube hypertrophy. CONCLUSION: The results confirmed that AS induces hypertrophy in myotubes through the PI3K/Akt/mTOR pathway.